Information feedback and contest structure in rent-seeking games - Francesco Fallucchi; Elke Renner; Martin Sefton (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
We investigate the effects of information feedback in rent-seeking games with two different contest structures. In the deterministic contest a contestant receives a share of the rent equal to her share of rent-seeking expenditures, while in the stochastic contest a contestant wins the entire rent with probability equal to her share of rent-seeking expenditures. In deterministic contests average expenditures converge to equilibrium levels when subjects only get feedback about own earnings, and additional feedback about rivals' choices and earnings raises average expenditures. In stochastic contests information feedback has an opposite, and even stronger, effect: when subjects only get feedback on own earnings we observe high levels of rent dissipation, usually exceeding the value of the rent, and additional feedback about rivals' choices and earnings has a significant moderating influence on expenditures. In a follow-up treatment we endogenize information feedback by allowing contestants in a stochastic contest to make "public" or "private" expenditures. Subjects make the vast majority of expenditures privately and overall excess expenditures are similar to the stochastic contest with own feedback.
Keywords: C72; C92; D72; 330; contests; rent-seeking; information feedback; learning; experiments